The roles and mechanisms of the m6A reader protein YTHDF1 in tumor biology and human diseases - Zuyao Chen; Xiaolin Zhong; Min Xia; Jing Zhong (Elsevier, 2021)
YTHDF1 is the most versatile and powerful reader protein of N6-methyladenosine (m6A)-modified RNA, and it can recognize both G(m6A)C and A(m6A)C RNAs as ligands without sequence selectivity. YTHDF1 regulates target gene expression by different mechanisms, such as promoting translation or regulating the stability of mRNA. Numerous studies have shown that YTHDF1 plays an important role in tumor biology and nontumor lesions by mediating the protein translation of important genes or by affecting the expression of key factors involved in many important cell signaling pathways. Therefore, in this review we focus on some of the roles of YTHDF1 in tumor biology and diseases.